Temporomandibular Joint Assessment of Pre and Post Prosthetic Treatment of Partially Edentulous Patient (Radiographic Examination) - Nadira A Hatim; Nazar Gh Jameel; Marwah M Shehab (University of Mosul, College of Dentistry, 2011)
Aims: This study investigates the condyle position in temporal fossa of completely and partially den-tated patients pre and post prosthetic treatment, and compares between right and left condyles in both groups by radiographic Examination. Materials and Methods: Twenty two completely dentate pa-tients (20-28) years old, and thirty partially dentate patients (35-65) years old meet the criteria of the study. For each patient a temporary removable acrylic partial denture was constructed. By using plan-meca digital radiography device (Finland), the radiograph for TMJ were taken by special panoramic technique in open and close mouth position for both groups (Pre, at, and Post insertion of dental pros-thesis). By using Dimaxis software program the linear measurements of the narrowest anterior and posterior joint spaces made by using program tools, the articular eminence inclination angle in closed mouth position also measured, and statistical analysis by using SPSS program version 11.5 for all data. Results: The results showed that in completely dentated patient, 76.5% had condyles in concentric po-sition, patients who had lost posterior teeth support showed a predominance of posterior condylar posi-tions and significant decreased in displacement after prosthodontic treatment (P=0.015 for right side and P=0.032 for left side) at significant level 0.05. Asymmetry in concentric position of condyle be-tween right and left side, but insignificant value P>0.05. There is significant difference in the inclina-tion of articular eminence angle between completely and partially dentate patients P=0.01 for the right side and P=.005for the left side. Conclusions: Posterior displacement of the condyle associated with loss of posterior teeth. Significant change in the condylar position occurred after prosthetic rehabilita-tion, patient's comfort obtained when the position of condyle in glenoid fossa is (concentric position + 0.35mm). The loss of teeth caused remodeling of articular eminence inclination.